Ph3P-mediated highly selective C(α)–P coupling of quinone monoacetals with R2P(O)H: convenient and practical synthesis of ortho-phosphinyl phenols. Issue 22 (25th October 2018) - Shen, Ruwei; Zhang, Ming; Xiao, Jing; Dong, Chao; Han, Li-Biao
Abstract : The Ph3 P-mediated C(α)–P coupling reaction of quinone monoacetals with secondary phosphine oxides is developed to provide an effective method for the synthesis of a wide array of ortho -phosphinyl phenols in good to excellent yields. Abstract : A highly selective Ph3 P-mediated C(α)–P coupling reaction of quinone monoacetals with secondary phosphine oxides is developed to provide an effective method for the synthesis of a wide array of ortho -phosphinylphenols in good to excellent yields. This protocol can be adopted for scale-up synthesis directly from cheap and abundant phenols, and the products can be easily obtained in high yields by simple filtration without the use of organic extraction or chromatography.